Considerations about race and identity in the conformation of Latin America - González Sancho, Roy (2023)
This essay aims to carry out a brief analysis of the conformation of Latin America. Among the results, it has been visualized the evident role that, confessional clashes and political-economic disputes between the colonizing countries have had in the implantation of relationships based on forms of hierarchization, segregation and discrimination of the Amerindian, Afro-descendant, and mestizo populations, during the process of conquest and the subsequent independence. Especially considering the need on the maintenance of the domination of the colonial powers and the subsequent colonial caste system in the periods of “independent” life. At the same time that it is urged, given the contemporary conditions, for the discussion and deep reflection of issues such as alter subjectivities and Otherness. In this way, an exposition of the subject is carried out, beginning with the repercussions and characteristics of the colonial era, followed by a review of the particularities and effects that occurred in the post-Independence times, to continue with an analysis of some current debates around subjectivities and identities, ending with a discussion on the conclusions of the process.